Impact of COVID-19 pandemic on training of pharmacy residents and fellows: Results from a national survey of postgraduate pharmacy trainees. (19th March 2021) - Moore, W Justin; Webb, Andrew; Morrisette, Taylor; Sullivan, Louisa K; Alosaimy, Sara; Hossain, Shahrier; Howe, Zachary; Vlashyn, Olga O; Paloucek, Frank P; Rybak, Michael J; Wang, Sheila K
Abstract: Purpose: The coronavirus disease 2019 (COVID-19) pandemic has impacted the activities of healthcare workers, including postgraduate pharmacy trainees. Quality training experiences must be maintained to produce competent pharmacy practitioners and maintain program standards. Methods: A cross-sectional survey of postgraduate pharmacy trainees in the United States was conducted to evaluate training experience changes and assess perceived impacts on residents and fellows following the COVID-19 pandemic's onset. Results: From June 4 through June 22, 2020, 511 pharmacy trainees in 46 states completed the survey. Participants' median age was 26 (interquartile range [IQR], 25-28) years, with included responses from postgraduate year 1 residents (54% of sample), postgraduate year 2 residents (40%), and postgraduate fellows (6%). Compared to experiences prior to the onset of the COVID-19 pandemic, fewer trainees conducted direct patient care (38.5% vs 91.4%, P < 0.001), more worked from home (31.7% vs 1.6%, P < 0.001), and less time was spent with preceptors per day (2 [IQR, 2-6] hours vs 4 [IQR, 1-4] hours, P < 0.001). Sixty-five percent of respondents reported experiencing changes in their training program, 39% reported being asked to work in areas outside of their routine training experience, and 89% stated their training shifted to focus on COVID-19 to some degree. Most respondents perceived either major (9.6%) or minor (52.0%) worsening in quality of experience, with major and minor improvement in quality of experience reported by 5.5% and 8.4% of respondents, respectively. Conclusion: Pharmacy resident/fellow experiences were perceived to have been extensively impacted by the COVID-19 pandemic in varying ways. Our findings describe shifts in postgraduate training and may aid in the development of best practices for optimizing trainee experiences in future crises.